Sosialisasi Penggunaan Teknologi Produksi dan Pemasaran Terasi Berdaya Saing Nasional Pada Masyarakat Desa Kuala Penaga Aceh Tamiang - Agustinar; Rafiza Zuliani; Suyani suryani (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2023)
The process of making shrimp paste in the people of Kuala Peunaga Village still uses a manual process with very minimal output, unattractive packaging and the marketing process still uses traditional methods, namely direct marketing and mouth to mouth so that the production of shrimp paste in the village has not been touched by the outside community is a problem that drives the existence of socialization activities in the form of this service. This activity aims to provide educational knowledge about the importance of using modern technology in the shrimp paste production process and marketing through digital media by utilizing social media. The implementation method is by outreach to the community starting with observation, implementation of activities, monitoring and evaluation as well as ongoing support. After the implementation of this activity, the community is very enthusiastic about using modern technology and will promote their products by digitalization or through social media. This socialization is also highly expected by the community so that later there will be special training and assistance to develop the shrimp paste business of the people of Kuala Peunaga Village into a nationally competitive product.